Response of Maize Seedlings to Cadmium Application after Different Time Intervals. (2nd June 2013) - Hussain, Iqbal; Akhtar, Shamim; Ashraf, Muhammad Arslan; Rasheed, Rizwan; Siddiqi, Ejaz Hussain; Ibrahim, Muhammad
Abstract : Present study was conducted to appraise the inhibitory effects of cadmium applied at different time intervals on various growth and biochemical parameters in two maize lines, Maize-TargetedMutagenesis 1 and 2 (MTM-1 and MTM-2). Twenty-day-old seedlings were exposed to 0, 3, 6, 9, and 12 mg CdCl2 kg −1 sand. Both maize lines exhibited significant perturbations in important biochemical attributes being employed for screening the crops for cadmium tolerance. The results showed that a higher concentration of cadmium (12 mg CdCl2 kg −1 ) considerably reduced the plant growth in line MTM-1 on the 5th, 10th, and 15th day after the treatment. In contrast, irrespective of exposure time, the plant biomass and leaf area did not show inhibitory effects of cadmium, specifically at 3 mg CdCl2 kg −1 in line MTM-2. In addition, MTM-2 was found to be more tolerant than line MTM-1 in terms of lower levels of hydrogen peroxide (H2O2), malondialdehyde (MDA) contents, and relative membrane permeability (RMP). Moreover, H2O2, MDA, RMP, and anthocyanin increased at all levels of cadmium in both lines, but a significant decline was observed in photosynthetic pigments, total free amino acids, and proline contents in all treatments particularly on the 10th and 15th day after treatment.